STRATEGI RELAKSASI UNTUK MEMBANTU SISWA YANG MENGALAMI STRES BELAJAR DI KELAS 9D SMP NEGERI 1 MEJAYAN KABUPATEN MADIUN - Pramunto, Bambang Agus (Jurnal Counsellia, 2015)
Along with the advancement of science and technology, the problems faced by individuals increasingly complex. A problem that can not be avoided by students in general and students in grade 9 in particular is a matter of learning. Slowly but surely grade 9 students have to face the